High impact journal writing and publication - Md. Abdul, Maleque (2021)
Writing a research article in order to publish it in a high-impact journal is a crucial part of making sure your research is worthy and has an impact outside your organization. There are, however, systematic steps for writing a quality scientific research manuscript that can lead to successful publication without rejection. It’s not difficult to know where to start, and daunting to decide which of the numerous procedures that are available today that help a researcher to suit best for a joyous moment with publication. This workshop is designed to share a systematic approach to writing and publication in high-impact journals with a case example and help you get your research publication.